Sharp recanalization of the brachiocephalic vein occlusion through the external jugular vein in hemodialysis patients - Zhao, Yuliang (Ann Transl Med, 2020)
BACKGROUND: Although the internal jugular vein (IJV) is the most widely used puncture site in hemodialysis catheter insertion and central vein angioplasty, the external jugular vein (EJV) offers an alternative vascular access point in cases when the IJV is inaccessible. The present study aims to observe the efficacy and safety of sharp recanalization of the brachiocephalic vein occlusion through the EJV in hemodialysis patients. METHODS: This retrospective study enrolled a cohort of hemodialysis patients who received sharp recanalization of occlusive brachiocephalic vein through the EJV at a university-affiliated hospital between January 2017 and January 2019. The demographic information and clinical outcome data of the patients were collected and analyzed. RESULTS: A total of 16 hemodialysis patients who received right brachiocephalic vein sharp recanalization through the EJV were analyzed. The technical success rate was 100%. Twelve patients (12/16, 75%), whose EJV-subclavian vein angle (E-S angle) was 60–80 degrees, were successfully recanalized on the first attempt. With the other 4 patients (4/16, 25%), whose E-S angle approached 90 degrees, the brachiocephalic vein was recanalized on the second attempt by elevating the ipsilateral shoulder, therefore decreasing the E-S angle to align the course of the EJV with the brachiocephalic vein. Three minor complications were recorded, including 1 patient with blood continuously oozing from the EJV at the puncture site and 2 patients with mild chest pain. After an average of 10 months of follow-up, the clinical patent rate was 81.25% with no procedure-related complications reported. CONCLUSIONS: Sharp recanalization through the EJV could be an effective and safe alternative treatment for right brachiocephalic vein occlusion in hemodialysis patients if performed by an experienced practitioner. Measuring the angle formed by the EJV and the subclavian vein might provide helpful information for selecting patients.